Getting a Grip: The PET Framework for Studying How Reader Emotions Influence Comprehension. Issue 5 (4th July 2019) - Bohn-Gettler, Catherine M.
ABSTRACT: Comprehension models do not often account for the multifaceted and emotionally charged nature of reading in real-world settings. In addition, studies of how reader emotions influence comprehension often yield conflicting findings due to lack of specificity regarding the process, emotion, and task under investigation. The PET (P rocess, E motion, T ask) framework considers how reader emotions differentially influence comprehension as a function of the specific comprehension process, type of emotion, and task features. It offers testable hypotheses regarding the influence of reader emotion for levels in the tripartite theory, resonance, integration and validation, inferences, and coherence-based retrieval. It also considers how important interactions arise through text, reader, and activity variables. Therefore, the particular comprehension process, the specific emotion, and varying task features can lead to different predictions regarding the effects of emotion on comprehension processes. The PET framework provides organization to guide research and clarify understandings regarding how to support readers.